Spanning tree modulus for secure broadcast games. Issue 3 (21st April 2020) - Albin, Nathan; Kottegoda, Kapila; Poggi‐Corradini, Pietro
Abstract: The theory of p ‐modulus provides a general framework for quantifying the richness of a family of objects on a graph. When applied to the family of spanning trees, p ‐modulus has an interesting probabilistic interpretation. In particular, the 2‐modulus problem in this case has been shown to be equivalent to the problem of finding a probability distribution on spanning trees that utilizes the edges of the graph as fairly as possible. In the present work, we use this fact to produce a game‐theoretic interpretation of modulus by employing modulus to solve a secure broadcast game.